(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article explores the transformative impact of innovative technologies on foreign language education, highlighting key advancements such as AI-powered learning apps, virtual and augmented reality tools, gamification, and online collaboration platforms. It emphasizes how these technologies enhance engagement, adaptability, and practical skill development for learners. The article also discusses the integration of speech recognition tools, translation AI, and adaptive learning platforms that personalize the educational journey. The conclusions underscore the importance of blending technological innovation with traditional teaching methods to create a comprehensive and effective language learning experience, ultimately fostering global communication and cultural understanding